Reconstructing Gen-Z Character through Tauhid and Ibn Khaldun's Ashabiyah: Toward Social Cohesion in the Digital Era - Taswiyah Taswiyah; Ilzamudin Ilzamudin; Suadi Sa'ad; Ayatullah Humaeni (Journal of General Education and Humanities, 2026)
Generation Z (Gen-Z) faces a character crisis in the digital era, marked by moral decline, dependence on social validation, and weakening social cohesion. This study aims to reconstruct a Gen-Z character by integrating Tauhid as a spiritual foundation and Ibn Khaldun’s concept of Ashabiyah as a social force. Previous studies discussed Tauhid and Ashabiyah separately, but no study has integrated both as a holistic paradigm for character reconstruction in the digital era. This research employs a qualitative method through library research and content analysis. The findings show that the crisis is caused not only by technological disruption but also by weak internalisation of value and declining social solidarity. Tauhid develops responsible, resilient, moral, and independent individuals through Muraqabah and Izzah, while Ashabiyah strengthens social cohesion and collective resilience based on religious values (ad-din). Their integration produces four stages of character formation: Bashar, Qolb, Fana-Baqa, and Malakah. This study also finds that the Tafakur and Tadabur methods are effective in integrating science, technology, and spiritual values. Tafakur encourages reflective thinking based on revelation, while Tadabur emphasises ethical awareness and the purpose of human activities. This study offers a holistic paradigm for Gen-Z character education that integrates spiritual morality, social cohesion, and epistemological reconstruction to address digital challenges.